2012
DOI: 10.1002/job.1833
|View full text |Cite
|
Sign up to set email alerts
|

Positive affectivity neutralizes transformational leadership's influence on creative performance and organizational citizenship behaviors

Abstract: SummaryThis study uses an interactionist approach to examine the moderating effect of follower trait positive affectivity (trait PA) on the relation between transformational leadership and both follower creative performance and organizational citizenship behaviors (OCB). On the basis of responses from 212 employees and their direct supervisors from the research and development department of a company in Mainland China, results support the hypothesized moderation effect. Specifically, the positive influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 66 publications
2
65
0
3
Order By: Relevance
“…Previous studies found that positive psychological capacities such as positive affect (Gilmore et al, 2013), role breadth self-efficacy (Den Hartog and Belschak, 2012), and core self-evaluations (Nübold et al, 2013) may also act as substitutes for transformational leadership. The finding that mindfulness, which is considered to be a trainable metacognitive skill (Hülsheger et al, 2013(Hülsheger et al, , 2015Shapiro et al, 2007), is also able to compensate for a low levels of transformational leadership is an important contribution to the substitutes for leadership theory (Kerr and Jermier, 1978;Podsakoff et al, 1996), providing actionable strategies for organizations seeking to foster employees' intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that positive psychological capacities such as positive affect (Gilmore et al, 2013), role breadth self-efficacy (Den Hartog and Belschak, 2012), and core self-evaluations (Nübold et al, 2013) may also act as substitutes for transformational leadership. The finding that mindfulness, which is considered to be a trainable metacognitive skill (Hülsheger et al, 2013(Hülsheger et al, , 2015Shapiro et al, 2007), is also able to compensate for a low levels of transformational leadership is an important contribution to the substitutes for leadership theory (Kerr and Jermier, 1978;Podsakoff et al, 1996), providing actionable strategies for organizations seeking to foster employees' intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Transformational leaders who 'walk the talk', treat their followers fairly and show that they trust them, along with taking an interest in their individual well-being, are more likely to see similar behaviours replicated by the workforce. Such leaders generate enthusiasm amongst followers to display prosocial activities such as OCBs, as they provide a role model for them to follow (Gilmore et al 2012). When transformational leaders display inspirational motivation and intellectual stimulation they will provide an environment in which followers feel positive about their tasks at hand.…”
Section: Transformational Leadership and Ocbsmentioning
confidence: 99%
“…Creative performance of employees and OCB have been identified as advantageous for organizations (Gilmore et al 2013). According to Smith et al (1983), OCB provides employees making innovative suggestions and Van Dyne et al (1995) assert that employees make creative suggestions to co-workers by the help of OCB.…”
Section: Organizational Citizenship Behavior and Its Relation With Inmentioning
confidence: 99%